2019
DOI: 10.1097/wco.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Advances in primary mitochondrial myopathies

Abstract: Purpose of review Although mitochondrial diseases impose a significant functional limitation in the lives of patients, treatment of these conditions has been limited to dietary supplements, exercise, and physical therapy. In the past few years, however, translational medicine has identified potential therapies for these patients. Recent findings For patients with primary mitochondrial myopathies, preliminary phase I and II multicenter clinical trials of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Mitochondrial myopathies encompass a broad and heterogeneous group of rare genetic progressive conditions caused by mutations in genes in the nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) that impair the oxidative phosphorylation (OXPHOS) in the mitochondria (67,68). The consequence is a deficit in energy production in the form of adenosine triphosphate (ATP), with muscles being the most affected tissue.…”
Section: Metabolic Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial myopathies encompass a broad and heterogeneous group of rare genetic progressive conditions caused by mutations in genes in the nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) that impair the oxidative phosphorylation (OXPHOS) in the mitochondria (67,68). The consequence is a deficit in energy production in the form of adenosine triphosphate (ATP), with muscles being the most affected tissue.…”
Section: Metabolic Myopathiesmentioning
confidence: 99%
“…The consequence is a deficit in energy production in the form of adenosine triphosphate (ATP), with muscles being the most affected tissue. Mitochondrial myopathies rarely manifest with acute myalgia and myoglobinuria, such as in complex I, III (cytochrome b) and IV (cytochrome c oxidase or COX) (61,68,69). However, recurrent exercise intolerance and premature fatigue are frequently reported in mitochondrial myopathies.…”
Section: Metabolic Myopathiesmentioning
confidence: 99%
“…[100][101][102][103][104][105] Previous studies have shown that SS-31 may decrease oxidative stress, 106 protect against ischemia-reperfusion injury, 107 and improve mitochondrial efficiency. 108 SS-31 is currently being evaluated in clinical trials for treatment of heart failure, 109 primary mitochondrial myopathies, 110 and stent revascularization in atherosclerotic renal artery stenosis. 111 In addition to mitochondrial structure protection, some studies also have reported that SS-31 could repair damaged mitochondria.…”
Section: Mitochondrial Protectants As Therapeutic Agentsmentioning
confidence: 99%
“…Secondary involvement of mitochondria was frequently observed in multiple neuromuscular diseases. The physiological functions of elamipretide 50,51 are the restoration of adenosine triphosphate production together with decreased reactive oxygen species emission and electron carriers back together with an higher membrane curvature resulting in normalized cardiolipin content. In the MMPOWER study, 30 patients in the elamipretide dosing groups (n = 9 with 0.01 mg/kg/h elamipretide, n = 9 with 0.1 mg/kg/h elamipretide, and n = 9 with 0.25 mg/kg/h elamipretide) compared with 30 patients in placebo group were included.…”
Section: Clinical Trials and New Treatment Targetsmentioning
confidence: 99%